Stilbene Glycosides in Pinus cembra L. Bark: Isolation, Characterization, and Assessment of Antioxidant Potential and Antitumor Activity on HeLa Cells - Lungu, Cristina; Mihai, Cosmin-Teodor; Vochita, Gabriela; Gherghel, Daniela; Mangalagiu, Ionel I; Gafton, Mihaela; Miron, Sorin-Dan; Iurciuc Tincu, Camelia-Elena; Nahar, Lutfun; Sarker, Satyajit D; Miron, Anca (Plants (Basel, Switzerland), 2025)
Stilbenes are plant secondary metabolites with remarkable antidiabetic, anti-inflammatory, antimicrobial, antioxidant, antitumor, and neuroprotective properties. As these compounds are valuable constituents in healthcare products and promising drug candidates, exploring new sources of stilbenes is essential for therapeutic advancement. The present study reports the isolation of two stilbene glycosides, resveratroloside and pinostilbenoside, from Pinus cembra L. bark. Their antioxidant activity and cytotoxic effects against HeLa cells were evaluated in comparison to the raw bark extract. The structures of resveratroloside and pinostilbenoside were confirmed by nuclear magnetic resonance (NMR) and mass spectrometry (MS) data analyses. Antioxidant activity was assessed by 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging and reducing power assays. Cell viability, apoptosis, cell proliferation, and cell cycle assays were used to evaluate the cytotoxic potential against HeLa cells. Resveratroloside and pinostilbenoside exhibited lower activity as free radical scavengers and reducing agents. However, they showed greater efficacy in reducing viability and suppressing proliferation in human cervical carcinoma HeLa cells. Given the promising findings of our study, the therapeutic potential of resveratroloside and pinostilbenoside should be further investigated.
Keywords: HeLa cells; antioxidant activity; pinostilbenoside; resveratroloside; antitumor activity; bark extract; Pinus cembra L.